Denial and Alarmism in Collective Action Problems - Manuel Förster; Joël J. van der Weele (Tinbergen Institute, 2018)
We analyze communication about the social returns to investment in a public good. We model two agents who have private information about these returns as well as their own taste for cooperation, or social preferences. Before deciding to contribute or not, each agent submits an unverifiable report about the returns to the other agent. We show that even if the public good benefits both agents, there are incentives to misrepresent information. First, others' willingness to cooperate generates an incentive for “alarmism”, the exaggeration of social returns in order to opportunistically induce more investment. Second, if people also want to be perceived as cooperators, a “justification motive” arises for low contributors. As a result, equilibrium communication features “denial” about the returns, depressing contributions. We illustrate the model in the context of institutional inertia and the climate change debate.
Keywords: C72; D64; D82; D83; D91; 330; cheap talk; cooperation; image concerns; information aggregation; public goods